Introducing Adaptivity and Collaborative Support into a Web-Based LMS - Bozic, Natasa Hoic; Mornar, Vedran; Boticki, Ivica (Computing and Informatics, 2012)
In this paper the design and implementation of AHyCo (Adaptive Hypermedia Courseware), a web-based learning management system based on adaptive hypermedia, is described. AHyCo consists of a domain model, a student model, an adaptive model and a collaborative model. AHyCo supports interaction between students and content by using adaptive hypermedia and online tests. Particular attention is given to the design of the collaborative functionality which enables automatic grouping of students based on various criteria. Furthermore, student to student and student to teacher interaction is supported through asynchronous communication (forum). File sharing and inter-group grading and evaluation modules were introduced into the collaborative module as well enticing interaction between students across groups.